Examining the Implementation of Hibah BERMASA Program for Village Development - Anjelita Ramodhani; Nurhazana Nurhazana (Jurnal Akuntansi Bisnis, 2023)
Bengkalis Regency Government issued the BERMASA village program for village development or village infrastructure. The Implementation of village development refers to the regulation of National Public Procurement Agency (NPPA) of the Republic of Indonesia Number 12 on 2019 concerning procurement of Good/Services in villages. The study aims to analyse the implemention process, consider priorities and optimize village government efforts. The type of research is descriptive qualitative research. The sampling technique used purposive sampling in order to obtain 8 villages. The Results of this study find the implementation of village development or village infrastructure had been partially self-management in accordance with regulations for the procurement of goods/services in the village. The priority for village development or village infrastructure is based on the BERMASA village program regulations on considerations of needs, benefits, regional development and the RPJMDes. Optimizing village government through accelerating the implementation and negotiation process, as well as inflation. This research is and evaluation for the village government for the BERMASA Village Program.